INTENSITAS PENGGUNAAN JALAN HUTAN SEBAGAI PRASARANA PENGANGKUTAN KAYU DI TIGA PERUSAHAAN HUTAN DI JAMBI DAN KALIMANTAN SELATAN - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
This paper presents the results of an investigation on the use of forest roads as log transportation infrastructure at two logging companies in Jambi and one logging company in South Kalimantan carried out in 1990. The objective is to find out the information of the intensity of forest roads use as log transportation infrastructure. For that purpose, the data on forest road length (km) and actual log production (m3) for the period of between three and ten years were collected. The results reveal that:1. Forest roads at several forest companies in Sumatra and Kalimantan were commonly unpaved, and therefore, can only be used when they are dry.2. The average lengths of forest roads built by A, B and C companies were 6.050 km/year with the range of between 2.000 and 13.000 km/year; and 12. 733 km/year with the range of between 7.600 and 19.800 km/year; 11.275 km /year with the range of between 2: 565 and 22. 650 km /year, respectively.3. Actual log production ranged from 18,045,48 to 45,555.60 m3 /year with the average of 27,249.88 m3 /year for A company; from 19,484.07 to 41,526.29 m3 /year with the average of 31,485.36 m3 /year for B company; and from 15,892.25 to 54,553.95 m3 /year with the average of 36,745.30 m3 /year for C company.4. Correction factor to be used in calculating actual production from target production at A, B and C companies were respectively 0. 74 with the range of between 0.36 and 0.98; 0.97 with the range of between 0.96 and 0.99; and 0. 76 with the range of between 0.32 and 1.09.5. The intensity of forest roads use as log transportation infrastructure at A, B and C forest companies range between 1,503. 79 and 17,234.05 m3 / km-year with the average of 7,165. 73 m3 / km-year; between 984.04 and 4,400. 75 m3 / km-year with the average of 3,076.61 m3 / km-year; and between 1,352.53 and 13,292. 74 m3 / km- year with the average of 5,147.53 m3 / km-year, respectively.